Capsid control for organic cocoa in Ghana : - Ayenor, Godwin Kojo (Troical Resource Management Papers, 2006)
Cocoa is important foreign exchange earner for Ghana. However, compared to Ivory Coast and Malaysia, two other major producing countries, yields are extremely low. The causes of low yields are many. They include low producer price offered until recently by the government, costs of labour, poor tree husbandry practices, and pest and diseases. The recent increase in producer price has rekindled farmers' interest in measures that can help them address low yields especially in pest and disease control.